The Analysis of Characters’ Speech Acts in Hills Like White Elephants - Jiahong, Ren (Advances in Social Sciences Research Journal, 2017)
Hills Like White Elephants is a famous classic novel written by Ernest Miller Hemingway in 1927. The novel is extremely short, only 1455 words. The most important character of the novel is that the short story reveals figures’ spirits in the form of daily dialogues. Therefore, this article intends to study the conversations and behaviors from the perspective of Speech Act Theory to explore how the writer portrayed the two typical characters. Speech Act Theory is an important theory in the study field of pragmatics, which was proposed by Austin in 1955 and then was developed by Searle. Therefore, this article will analyze Hemingway’s short novel Hills Like White Elephants from speech act theory perspective, such as from it’s speech and acts. Thus we will have a better understanding about the characters’ relationship in the novel and the author’s purposes in writing this novel. And the author’s writing features will be reproduced, as well as the topic of the novel, the way of the language expressions and the relation of the significance. Above all, we can see that Speech Act Theory plays an important role in analyzing utterances in the novel. The analysis of the speech acts of the characters in Hills Like White Elephants can not only help people understand this novel but also provide materials to study this classical novel in new field. It is also hoped that the analysis of Hills Like White Elephants will arouse an important way to the appreciation of other classical novels.